PSYCHOLOGICAL CHARACTERISTICS OF THE INFLUENCE OF SATISFACTION WITH FAMILY LIFE ON EMOTIONAL INTELLIGENCE (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the psychological characteristics of the impact of family life satisfaction on emotional intelligence. Based on scientific data, the author studied and analyzed the specific aspects of the psychological characteristics of the effect of family life satisfaction on emotional intelligence based on available literature.